2019
DOI: 10.1002/ejic.201900306
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Substituted Polyoxometalates as α‐Glucosidase Inhibitors

Abstract: α‐Glucosidase inhibitors slow the digestion of carbohydrates and reduce blood sugar levels after meals. Recently, our experimental team found that phosphomolybdic acid with a Dawson‐type structure can effectively inhibit the activity of α‐glucosidase. Dawson‐type phosphomolybdic acid {H6(P2Mo18O62), H8[P2Mo17Fe(OH2)O61], H8[P2Mo17Co(OH2)O61] and H8[P2Mo17Ni(OH2)O61] abbreviated as P2Mo18, P2Mo17Fe, P2Mo17Co and P2Mo17Ni} were synthesized, and their inhibitory potential for α‐glucosidase was evaluated by enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…As a comparison, both K m and V max values of compounds 2 and 6 decreased with the increment of concentration. From the abovementioned analysis, they were deduced as mixed-type inhibitors against α-glucosidase. , By the secondary plots of the slope and intercept versus concentrations, their K i values (the inhibition constant of the free enzyme) were calculated as 13.0, 11.7, 2.9, and 5.3 μM and K is values (the inhibition constant of the enzyme–substrate complex) were 21.5, 4.1, 1.2, and 54.6 μM. The K is values of 1 and 11 were larger than their K i values, indicating the priority in binding with the free enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…As a comparison, both K m and V max values of compounds 2 and 6 decreased with the increment of concentration. From the abovementioned analysis, they were deduced as mixed-type inhibitors against α-glucosidase. , By the secondary plots of the slope and intercept versus concentrations, their K i values (the inhibition constant of the free enzyme) were calculated as 13.0, 11.7, 2.9, and 5.3 μM and K is values (the inhibition constant of the enzyme–substrate complex) were 21.5, 4.1, 1.2, and 54.6 μM. The K is values of 1 and 11 were larger than their K i values, indicating the priority in binding with the free enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] More intriguingly, one of the important biological applications of POMs is their ability to cause the inhibition of certain enzymes. 31 Our group has previously confirmed that Keggin-type POMs can be excellent inhibitors of α-glucosidase [32][33][34] and tyrosinase [35][36][37][38] , and, among them, H 3 PMo 12 O 40 possesses the strongest inhibitory effect on these two enzymes. However, it remains unclear whether Keggin-type POMs will exhibit optimal effects in vivo.…”
Section: Introductionmentioning
confidence: 91%
“…多金属氧酸盐(简称多酸)是由氧原子桥接的 d 0 或 d 1 金属离子组成的过渡金属氧化物簇, 由处于最高氧化状 态的早期过渡金属元素(Mo、 W、 V、 Nb 等)组成 [23][24] . 由 于其独特的形状和负表面电荷 [25][26][27][28] , 多酸通过共价键、 氢键和范德华力特异性地结合到各种生物分子上, 从而 发挥其生物活性 [29][30][31] , 过去几十年中, 多酸被用于治疗 炎症性肠病 [32] 、皮肤色素沉着 [33][34] 、肿瘤 [35][36][37][38] 、流感 [39] 和艾滋病毒 [40] 、糖尿病 [41] 、哮喘 [42] 、急性肾损伤 [43] 、 脑缺血/再灌注损伤 [44] , 甚至阿尔茨海默病 [45][46][47] . 先前 的研究发现, 多酸在体外对酪氨酸酶具有良好的抑制作 用 [48][49] [50][51] 一致.…”
Section: 引言unclassified